Signal-to-noise ratio of a mouse brain (13) C CryoProbe system in comparison with room temperature coils: spectroscopic phantom and in vivo results. - Wetterling, Friedrich (My University, 2014)
MRI and MRS in small rodents demand very high sensitivity. Cryogenic transmit/receive radiofrequency probes (CryoProbes) designed for (1) H MRI of mouse brain provide an attractive option for increasing the performance of small-animal MR systems. As the Larmor frequency of (13) C nuclei is four times lower than that for (1) H nuclei, an even larger sensitivity improvement is expected for (13) C applications. The aim of this work was to evaluate the performance of a prototype (13) C CryoProbe™ for mouse brain MRS. To investigate the possible gain of the (13) C CryoProbe™, we acquired localized single-voxel (13) C spectra and chemical shift images of a dimethyl sulfoxide phantom with the CryoProbe™, as well as with two room temperature resonators. The cryogenically cooled resonator achieved approximately four-fold higher signal-to-noise ratio in phantom tests when compared with the best-performing room temperature coil. In addition, we present localized (13) C spectra of mouse brain obtained with the CryoProbe™, as well as with one of the room temperature coils, demonstrating the performance in vivo. In summary, the cryogenic cooling technique significantly enhances the (13) C signal sensitivity at 9.4 T and enables the investigation of metabolism within mouse brain.
PUBLISHED
Keywords: 13C spectroscopy; CryoProbe™; MRS; SNR comparison; cryogenic coil; mouse; Neuroscience; Next Generation Medical Devices